2010
DOI: 10.3109/0886022x.2010.510232
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic 2009 influenza H1N1 virus vaccination: compliance and safety in a single hemodialysis center

Abstract: Background: Acceptance of vaccination against pandemic 2009 H1N1 influenza virus has been poor in some countries, perhaps because of concerns about safety of the new vaccine. Subjects and methods: We prospectively examined vaccination compliance and reasons for nonvaccination in the dialysis patients and the staff of a single hemodialysis unit, after on-site vaccination with a monovalent inactivated adjuvanted H1N1 vaccine. Safety profile was evaluated and compared to that of a control group without chronic ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
(11 reference statements)
2
1
0
Order By: Relevance
“…32 -35 A history of any prior influenza vaccination was the strongest predictor for receiving an influenza vaccination in the latest season in our study. This corresponds to other studies 15,21,36 ; if people are introduced to immunization and positive about it, they probably will continue to vaccinate. This behavior is also found in other patient populations such as elderly or rheumatic patients.…”
Section: Discussionsupporting
confidence: 83%
“…32 -35 A history of any prior influenza vaccination was the strongest predictor for receiving an influenza vaccination in the latest season in our study. This corresponds to other studies 15,21,36 ; if people are introduced to immunization and positive about it, they probably will continue to vaccinate. This behavior is also found in other patient populations such as elderly or rheumatic patients.…”
Section: Discussionsupporting
confidence: 83%
“…In agreement with other experience in dialysis patients (17), minor side effects were reported by most vaccinated individuals, but there were no serious adverse events. Although the augmentation of cellular alloimmunity in transplant recipients after influenza vaccination is well described (18), we did not detect any effect on graft function after vaccination in our patients.…”
Section: Discussionsupporting
confidence: 76%
“…The most frequent concern cited across studies was the opinion that these vaccines could have dangerous adverse reactions [27][28][29][30][31][77][78][79][81][82][83][84][85][86][87][88][89][90]92,[94][95][96][97][98][99][100][101][102][103]. This was often explained by study participants as a perception that these new vaccines were developed too quickly [80,100], resulting in insufficient testing and evidence [31,80,85,86,93,94,98,100,102] and information about long term adverse reactions [82,83,93,95,96]. Studies reported that concerns about inadequate testing also resulted in perceptions of low vaccine effectiveness [32,79,…”
Section: Pandemic Influenza Vaccinesmentioning
confidence: 99%